2022
DOI: 10.1038/s41598-022-17990-7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of third vaccine dose for coronavirus disease 2019 during the Omicron variant pandemic: a prospective observational study in Japan

Abstract: The administration of a third booster dose of messenger ribonucleic acid (mRNA) vaccines against coronavirus disease 2019 (COVID-19) has progressed worldwide. Since January 2022, Japan has faced a nationwide outbreak caused by the Omicron variant, which occurred simultaneously with the progression of mass vaccination with the third booster dose. Therefore, this study evaluated the effectiveness of the third dose of vaccine by reverse transcription-polymerase chain reaction (RT-PCR) test using nasopharyngeal sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…Several studies conducted during the Omicron surge in the general population, demonstrated the benefit of a booster dose (third or fourth) when administered in close proximity to the infection but effectiveness loss with time. [35][36][37][38] In an analysis of immunocompromised patients during the Omicron predominance, vaccine effectiveness against COVID-19-related hospitalization was highest between 7 and 89 days after the booster dose, 39 which is in accordance with our results. Studies in patients with lymphoproliferative disease did not find a correlation between vaccine status and COVID-19-related outcomes, although the timing of vaccination was not specified in these studies.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies conducted during the Omicron surge in the general population, demonstrated the benefit of a booster dose (third or fourth) when administered in close proximity to the infection but effectiveness loss with time. [35][36][37][38] In an analysis of immunocompromised patients during the Omicron predominance, vaccine effectiveness against COVID-19-related hospitalization was highest between 7 and 89 days after the booster dose, 39 which is in accordance with our results. Studies in patients with lymphoproliferative disease did not find a correlation between vaccine status and COVID-19-related outcomes, although the timing of vaccination was not specified in these studies.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies on the effectiveness of the third dose of the vaccine found improved efficacy against SARS-CoV-2 infection and a reduction in hospitalization [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. However, most studies on the effect of the third vaccination have been limited to a relatively short period of time after the third dose, and few longitudinal analyses of the effects of the third vaccination with an anti–SARS-CoV-2 vaccine have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The third booster dose elicits a high immune response against infection [ 6 , 7 ]. A field study demonstrated that the third dose increased vaccine effectiveness against disease severity [ 8 , 9 ], and reduced hospitalization rates [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%